Study Of Social Phenomenon Of Early Marriage In Beutong Nagan Raya Regency, Aceh, Indonesia - MAIFIZAR, AFRIANI; KEMALA SARI, PUTRI; MUHAMMAD, ZIKRI; ROTIN DJUSFI, APRI; BASRI, BASRI (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This article study the social phenomena of early marriage from a cultural and customary law perspective, providing adolescents with a great understanding of maintaining eastern culture, preserving local cultural values by filtering the current of globalization and providing knowledge about the impact of early marriage on their rculture, manteining family integrity. Therefore, we recommend that the community carry out a socialization on the importance of maintaining local cultural knowledge and wisdom about preparing for marriage in adulthood.RESUMEN Esta investigación estudia los fenómenos sociales del matrimonio precoz desde una perspectiva cultural y de derecho consuetudinario, brindando una gran comprensión a los adolescentes hacia el mantenimiento de la cultura oriental, preservando los valores culturales locales al filtrar la corriente de la globalización, y proporcionando, conocimiento sobre el impacto del matrimonio precoz en la cultura, manteniendo la integridad familiar. Por lo tanto, recomendamos a la comunidad llevar a cabo una socialización sobre la importancia de mantener la sabiduría y el conocimiento cultural local en la preparación del matrimonio en la edad adulta.